Promising outcomes of the PD-L1 inhibitor Socazolimab in recurrent and metastatic cervical cancer: a case report - Xu, Zichao; Wang, Minjie; Gong, Long; Luo, Guanghong; Zhang, Yucong; Zhou, Yayan; Li, Zihuang (Frontiers in Oncology, 2025)
Recurrent and metastatic advanced cervical cancer carries a poor prognosis, and there is currently no standardized treatment regimen. Immunotherapy, as an emerging and effective treatment strategy, has attracted significant attention. Socazolimab, a programmed death ligand 1 monoclonal antibody developed in China, is primarily used to treat patients with recurrent or metastatic cervical cancer who have failed or are intolerant to first-line platinum-based chemotherapy, regardless of programmed death ligand 1 expression status. We report the case of a Chinese patient with advanced cervical cancer and multiple metastases, who showed significant tumor regression after receiving Socazolimab treatment. Currently, during ongoing immunotherapy, the tumor continues to demonstrate persistent remission, with no new lesions observed. This case suggests that Socazolimab may offer a promising therapeutic option for patients with metastatic cervical cancer. In this report, the safety profile of Socazolimab was favorable, with no severe or uncontrollable adverse events. This case provides compelling evidence of the antitumor activity and manageable toxicity of Socazolimab in metastatic cervical cancer patients, offering valuable insights for further research and clinical application of the drug.